Global population genomics of the forest pathogen Dothistroma septosporum reveal chromosome duplications in high dothistromin‐producing strains. (1st April 2019) - Bradshaw, Rosie E.; Sim, Andre D.; Chettri, Pranav; Dupont, Pierre‐Yves; Guo, Yanan; Hunziker, Lukas; McDougal, Rebecca L.; Van der Nest, Ariska; Fourie, Arista; Wheeler, David; Cox, Murray P.; Barnes, Irene
Summary: Dothistroma needle blight is one of the most devastating pine tree diseases worldwide. New and emerging epidemics have been frequent over the last 25 years, particularly in the Northern Hemisphere, where they are in part associated with changing weather patterns. One of the main Dothistroma needle blight pathogens, Dothistroma septosporum, has a global distribution but most molecular plant pathology research has been confined to Southern Hemisphere populations that have limited genetic diversity. Extensive genomic and transcriptomic data are available for a D. septosporum reference strain from New Zealand, where an introduced clonal population of the pathogen predominates. Due to the global importance of this pathogen, we determined whether the genome of this reference strain is representative of the species worldwide by sequencing the genomes of 18 strains sampled globally from different pine hosts. Genomic polymorphism shows substantial variation within the species, clustered into two distinct groups of strains with centres of diversity in Central and South America. A reciprocal chromosome translocation uniquely identifies the New Zealand strains. Globally, strains differ in their production of the virulence factor dothistromin, with extremely high production levels in strain ALP3 from Germany. Comparisons with the New Zealand reference revealed that several strains are aneuploids; for example, ALP3 has duplications of three chromosomes. Increased gene copy numbers therefore appear to contribute to increased production of dothistromin, emphasizing that studies of population structure are a necessary adjunct to functional analyses of genetic polymorphisms to identify the molecular basis of virulence in this important forest pathogen.